Coronary Atherosclerosis The Implications of Being a Woman - Morales-Villegas, Enrique (Current Hypertension Reviews, 2013)
The profile of ischemic heart disease by coronary atherosclerosis has been developed based on clinical, paraclinical and angiographic grounds inherent to the male gender. A man in his 40s - 50s with
Keywords: coronary-angiotomography